(untitled) (Research, Society and Development, 2020)
The study aimed to evaluate the influence of reflective materials on the cultivation bench and the use of rice husks over the substrate in the formation of Dipteryxalata seedlings. The experiment was carried out in the experimental area of the Mato Grosso do Sul State University, in Cassilândia-MS, from November 1st, 2016 to January 26th, 2017. A completely randomized design in a 5 x 2 factorial scheme was used, with five replications and five plants per plot. Four reflective material for the cultivation bench and treatment without reflective material (control), combined with or without rice husks over the substrate (0.5 cm layer), were evaluated. Laminated paper tray, mirror, reflective fabric (known as “fake sequin fabric”), and aluminum foil were used as reflective materials. The reflecting materials did not differ in the reflectance of photosynthetically active radiation. However, the mirror and the aluminum foil reflected more than the control. The use of rice husk over the substrate did not increase the Dipteryxalata seedlings’ quality. The mirror as a reflective material produced Dipteryxalata seedlings of higher quality than the system without material reflector called control.